Valve-Sparing Aortic Root Replacement as First-Choice Strategy in Acute Type a Aortic Dissection - Aubin, Hug; Akhyari, Payam; Rellecke, Philipp; Pawlitza, Christina; Petrov, George; Lichtenberg, Artur; Kamiya, Hiroyuki (Frontiers in Surgery, 2019)
Background: Although, in theory, valve-sparing aortic root replacement (David procedure) is an ideal surgical option for acute aortic dissection type A (AADA) it is usually not regarded as the first-choice treatment due to the emergency setting and the relative complexity of the procedure. Here, we report the results of a consecutive, single-surgeon series of 45 AADA patients with the David procedure as first-choice treatment strategy. Methods and results: Between September 2009 and July 2013 a total of 49 patients with AADA were consecutively operated by the same surgeon at our institution. The David procedure was the treatment of choice for the proximal aorta unless aortic valve pathology or critical preoperative patient status advocated against it. Median follow-up was 5.0 years (CI95%, 4.0-6.0). Out of the 45 patients included in this study the David procedure was performed in 28 patients (62.2%), while in 17 patients (37.8%) an alternative surgical strategy had to be pursued. Although X-clamping (168.5 ± 41.7 vs. 110.3 ± 51.1 min; p=0.001), cardiopulmonary bypass (CPB) (245.0 ± 62.4 vs. 211.8 ±123 min; p=0.029) and total operation time (383.8 ±88.5 vs. 312.8 ± 144.8; p=0.047) were significantly longer in the David-group as compared to the non-David group, there was no difference in major complication rate as well as 30-day (17.9% vs. 23.5%; p=0.645) and 5-year mortality (28.6% vs. 35.3%) between groups. Conclusions: This small series indicates that the David procedure may be safe and feasible as a primary surgical treatment strategy for AADA.